Genomic insights into bamboo witches’ broom disease: pathogenicity and phytohormone biosynthesis in Aciculosporium take - Gu, Yu; Yu, Haoyue; Kuang, Jiayan; Ma, Xiaoping; Tahir, Muhammad Salman; He, Sainan; Liao, Yingchong (Frontiers in Microbiology, 2024)
Bamboo witches’ broom disease (WBD), caused by Aciculosporium take Miyake, devastates bamboo forests. Understanding the genome and pathogenic factors of pathogen is crucial for disease control. We employed single-molecule real-time sequencing, Illumina paired-end sequencing, and chromatin interaction mapping techniques to assemble the genome of A. take CCTCC-M2023413, analyze pathogenicity- and phytohormone-biosynthesis-related genes, and compare it to 12 other WBD pathogens. The genome of A. take is 59.24 Mb in size, with 54.32% repeats, 7 chromosomes, 7,105 protein-coding genes, 84 ribosomal RNAs, and 115 transfer RNAs. Predictive analysis of pathogenicity genes found 237 carbohydrate-active enzymes, 1,069 membrane transport proteins, 1,040 pathogen-host interaction genes, 315 virulence factors, and 70 effectors. Most of pathogenicity genes overlapped with repeat-rich regions. Additionally, 172 genes were linked to auxin biosynthesis, 53 to brassinosteroid biosynthesis, and 2 to cis-zeatin biosynthesis. Comparative genomic analysis identified 77 core orthogroups shared by 13 WBD pathogens, played roles in metabolites, genetic information processing, pathogenesis, cis-zeatin biosynthesis, lifespan, and quorum sensing. The miaA gene, crucial for cis-zeatin biosynthesis, is structurally conserved and sequence-diverse among 13 WBD pathogens, with upregulated expression during bamboo WBD pathogenesis. This highlights that cis-zeatin is significant contributor to host pathogenesis, and miaA is a new potential target for controlling WBD. This study provides important insights on preventing and controlling bamboo WBD.